International perspective on military exposure data sources, applications, and opportunities for collaboration - Hall, Amy L.; Batchelor, Trish; Bogaert, Laura; Buckland, Robert; Cowieson, Ali B.; Drew, Michael; Harrison, Kate; McBride, David I.; Schneiderman, Aaron; Taylor, Kathryn (Frontiers in Public Health, 2023)
Military personnel may be exposed to a range of hazards. The assessment, documentation and reporting of military exposure information are important steps to guide health protection, services, and research to support actively serving members and veterans. In 2021, a Working Group of researchers from veteran and defense administrations across the Five Eyes countries (Australia, Canada, New Zealand, the United Kingdom, and the United States) was established to examine large military exposure data sources available in each country, their applications, and opportunities to leverage information across administrations and internationally. We provide a brief summary of this work here to highlight some successful examples of data applications and to elicit interest in this evolving area of exposure science.